2015
DOI: 10.1093/icesjms/fsu249
|View full text |Cite
|
Sign up to set email alerts
|

Caribbean spiny lobsters equally avoid dead and clinically PaV1-infected conspecifics

Abstract: Social behaviour in Caribbean spiny lobsters (Panulirus argus) is mediated by conspecific chemical cues. These lobsters can be attracted to shelters emanating chemical cues from conspecifics but tend to avoid shelters emanating chemical cues from injured conspecifics, dead conspecifics, and conspecifics with visible signs of a potentially lethal disease caused by the pathogenic Panulirus argus virus 1 (PaV1). However, previous studies have not controlled for the presence of PaV1 (i.e. subclinical infection) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…However, when responses of test lobsters to WSSV infected conspecifics were compared to the responses of the healthy control animals, there was a significant increase in avoidance behavior (n = 56, p < 0.0001). Previous work by Behringer et al (2006) and Candia-Zulbarán et al (2015), using similar methods, have reported that lobsters aggregate with PaV1 infected conspecifics in only 20% of all trials [n = 20, p = 0.012; results from Candia-Zulbarán et al (2015)] and are detailed here for comparison (Fig 5) [29, 40]. This represents significant avoidance of PaV1 infected individuals when compared to 50% or random sheltering.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…However, when responses of test lobsters to WSSV infected conspecifics were compared to the responses of the healthy control animals, there was a significant increase in avoidance behavior (n = 56, p < 0.0001). Previous work by Behringer et al (2006) and Candia-Zulbarán et al (2015), using similar methods, have reported that lobsters aggregate with PaV1 infected conspecifics in only 20% of all trials [n = 20, p = 0.012; results from Candia-Zulbarán et al (2015)] and are detailed here for comparison (Fig 5) [29, 40]. This represents significant avoidance of PaV1 infected individuals when compared to 50% or random sheltering.…”
Section: Resultsmentioning
confidence: 56%
“…Panulirus argus also avoids dead conspecifics [40]. Avoidance of dead conspecifics may also occur through necromones, which are associated with decomposing organisms [40, 52, 53]. Avoidance of injured, dead, or diseased conspecifics results in a form of behavioral immunity, protecting against predation and disease via avoidance [11, 31, 5256].…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the lobsters that we sampled were found in experimental casitas, there is no evidence that the prevalence of PaV1 is any higher in areas where casitas are used [9,14,15,25]. This is probably because healthy lobsters avoid diseased conspecifics [17][18][19][20], and if forced to share a casita with a diseased lobster (e.g., due to the risk of predation), they tend to keep some distance from the diseased lobsters [40].…”
Section: Discussionmentioning
confidence: 92%
“…Although Caribbean spiny lobsters are gregarious, healthy lobsters tend to avoid heavily PaV1-infected conspecifics, which may help curb prevalence levels [17][18][19][20]. However, infections involve interactions not only between the pathogen and the host, but among networks of species [21].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the semi-open nature of the crustacean circulatory system, the change in the biosynthesis of this neuroactive compound could also affect the behavior and motility capabilities of the host (Giles and Usherwood, 1985;Stentiford et al, 1999). Considering that infected lobsters are avoided by healthy conspecifics (Behringer et al, 2011;Candia-Zulbarán et al, 2015), taurine could be tested as an odorant compound potentially mediating this social interaction (Giles and Usherwood, 1985).…”
Section: Discussionmentioning
confidence: 99%